2022
DOI: 10.4274/ejbh.galenos.2021.2021-5-4
|View full text |Cite
|
Sign up to set email alerts
|

De-Escalation of Breast Cancer Surgery Following Neoadjuvant Systemic Therapy

Abstract: Breast cancer treatment has seen many advances in recent decades, lessening the morbidity to patients, while improving outcomes. Central to these gains has been the introduction of breast conserving surgery and neoadjuvant systemic therapy (NST). There is a considerable interest in further de-escalation of the treatment of breast cancer, which is being studied in several ongoing randomised trials. We aimed to appraise the current literature regarding the various aspects of de-escalation of surgical treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
10
0
3
Order By: Relevance
“…In HER2-and TNBC-type breast cancer, NAC is the main line of treatment, given that it has prognostic value (depending on whether pCR is obtained by NAC) and that it aids in decision-making regarding changing postoperative treatment when preoperative results are ineffective [18][19][20]. Recent studies have reported high pCR rates in patients with a poor response to the initial chemotherapy after the drug was changed; consequently, attempts are being made to determine and predict drug response earlier [12]. If e cacy can be determined early in the regimen, patients who are or are not likely to achieve pCR can be predicted, and thus, whether the course of subsequent treatment needs to be changed can be determined [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HER2-and TNBC-type breast cancer, NAC is the main line of treatment, given that it has prognostic value (depending on whether pCR is obtained by NAC) and that it aids in decision-making regarding changing postoperative treatment when preoperative results are ineffective [18][19][20]. Recent studies have reported high pCR rates in patients with a poor response to the initial chemotherapy after the drug was changed; consequently, attempts are being made to determine and predict drug response earlier [12]. If e cacy can be determined early in the regimen, patients who are or are not likely to achieve pCR can be predicted, and thus, whether the course of subsequent treatment needs to be changed can be determined [12].…”
Section: Discussionmentioning
confidence: 99%
“…Such imaging might be conducted after two cycles of chemotherapy when using PET-CT or after one or two courses of chemotherapy when using contrast-enhanced breast MRI [6,7]. The timing of e cacy determination and the imaging modalities used in cases undergoing NAC are crucial as omitting surgery can be considered in cases where pCR is predicted [8][9][10][11][12]. Currently, imaging is conducted only once NAC is completed [13].…”
Section: Introductionmentioning
confidence: 99%
“…El uso cada vez más habitual de la quimioterapia neoadyuvante como tratamiento inicial de las pacientes con cáncer de mama (11)(12)(13), ha permitido que la mayoría de las pacientes con enfermedad loco-regional avanzada que consultan buscando atención médica, puedan ser intervenidas con base al efecto reductor sobre el tumor que tienen los diversos citostáticos. En este sentido, el manejo del cáncer de mama ha experimentado numerosos avances a lo largo del tiempo, disminuyendo los efectos adversos de los diversos tratamientos médico-quirúrgicos, así como mejorando los resultados a mediano y largo plazo (14)(15)(16).…”
Section: Discussionunclassified
“…Los beneficios de no hacer una disección axilar para ese pequeño grupo de pacientes con una fuerte respuesta a la quimioterapia neoadyuvante han sido demostrados en diversos ensayos clínicos (5,13,14,17,21), todos incluyen como parte del tratamiento, el empleo de radioterapia adyuvante. En nuestro caso, el servicio más cercano de radioterapia en funcionamiento y perteneciente al sector privado de la salud se encuentra a 170 Km de distancia (2 h aproximadamente de viaje en vehículo), igual ocurre en países de bajos ingresos (22)(23)(24)(25) este inconveniente dificulta dar cumplimiento con lo establecido en los diversos protocolos para el tratamiento del cáncer de mama (26,27).…”
Section: Discussionunclassified
See 1 more Smart Citation